An improved unit circuit model for transient heat conduction performance analysis and optimization in multi-layer materials. (25th January 2018) - He, Ke-Lun; Chen, Qun; Dong, En-fu; Ge, Wei-Chun; Hao, Jun-Hong; Xu, Fei
Graphical abstract: Highlights: Developed an improved unit circuit model for heat transfer analysis in multi-layer materials. This model incorporates interface nodes between every two adjacent layers for accuracy. Numerical results validate the accuracy compare to the finite volume method. Optimized the geometric structures of materials with this model and the genetic algorithm. Abstract: Transient heat conduction analysis and optimization in multi-layer thermal insulation materials (MLTIMs) requires an effective simplified model with certain accuracy. This paper proposes an improved unit circuit model (IUCM) based on the thermo-electrical analogy, where the interface nodes between every two adjacent layers are considered to describe the rapid variations of temperature gradients and heat fluxes at the interfaces. Then, the IUCM for three-layer materials is solved with jump and sinusoidal temperature boundaries, and the obtained temperatures and the outlet heat fluxes are compared to the solutions obtained by the finite volume method as well as other two existing lumped parameter models. The comparison shows that the IUCM reduces the relative mean outlet heat flux error by more than 50% compared to the other models in the studied cases. Applying the IUCM together with the genetic algorithm offers the optimal geometrical structures of three-layer materials, where the optimal structure reduced the outlet heat per unit area by more than 50% compared to the feasible structures. Meanwhile, arranging the mechanical layer with high thermal conductivity between two thermal insulation materials leads to a decrease of about 35% in the outlet heat during a certain time.